The water for food paradox. [Selected from the World Water Week, Stockholm, Sweden, 26-31 August 2012] - Chartres, Colin J.; Sood, Aditya (Elsevier, 2013)
This paper considers whether there will be sufficient water available to grow enough food for a predicted global population of 9 billion in 2050, based on three population and GDP growth modelling scenarios. Under the a low population growth with high GDP growth scenario, global consumptive water demand is forecast to increase significantly to over 6,000 km3, which is approximately 3,000 km3 greater that consumptive use in the year 2000. Also of concern is that rising global temperatures are going to increase potential evaporation, and t us irrigation water demand, by up to 17%. Sustainable intensification of agriculture can provide solutions to this predicament. However, productivity growth i not fast enough and we face considerable risks in the next 20 to 30 years. Concerted action to combat food insecurity and water scarcity is required based on agricultural research and development, policy reform and greater water productivity, if the world is to feed its growing population.